2004
DOI: 10.1007/s00253-004-1687-2
|View full text |Cite
|
Sign up to set email alerts
|

A novel N-carbamoyl-l-amino acid amidohydrolase of Pseudomonas sp. strain ON-4a: purification and characterization of N-carbamoyl-l-cysteine amidohydrolase expressed in Escherichia coli

Abstract: N-carbamoyl-L-cysteine amidohydrolase (NCC amidohydrolase) was purified and characterized from the crude extract of Escherichia coli in which the gene for NCC amidohydrolase of Pseudomonas sp. strain ON-4a was expressed. The enzyme was purified 58-fold to homogeneity with a yield of 16.1% by three steps of column chromatography. The results of gel filtration on Sephacryl S-300 and SDS-polyacrylamide gel electrophoresis suggested that the enzyme was a tetramer protein of identical 45-kDa subunits. The optimum p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 26 publications
0
17
2
Order By: Relevance
“…3747 [Wilms et al, 1999] and N-carbamoyl-L -cysteine amidohydrolase from Pseudomonas sp. ON-4a [Ohmachi et al, 2004]. The optimum temperature rises to 70 ° C for the thermostable microorganisms of B. stearothermophilus NS 1122A [Ishikawa et al, 1994] and B. kaustophilus CCRC 11223 [Hu et al, 2003].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…3747 [Wilms et al, 1999] and N-carbamoyl-L -cysteine amidohydrolase from Pseudomonas sp. ON-4a [Ohmachi et al, 2004]. The optimum temperature rises to 70 ° C for the thermostable microorganisms of B. stearothermophilus NS 1122A [Ishikawa et al, 1994] and B. kaustophilus CCRC 11223 [Hu et al, 2003].…”
Section: Discussionmentioning
confidence: 99%
“…Optimal pH values for the other L -N-carbamoylases range from pH 7.4 for B. kaustophilus CCRC 11223 to 8.5 for A. aurescens DSM 3747, while for N-carbamoyl-L -cysteine amidohydrolase from Pseudomonas sp. ON-4a it is more alkaline (pH 9.0) [Ohmachi et al, 2004].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…ON4a, which is more alkaline (pH 9.0). 25 Thermal stability studies performed on BsLcar have shown that maximun activity gradually decreases at temperatures over 65 C for 60 min, with 60% activity remaining after incubation at 70 C for 60 min. b-Ureidopropionase with L-N-carbamoylase activity from P. putida IFO 12996, which showed high thermostability, retaining 80% of initial activity after incubation at 65 C for 30 min.…”
Section: Temperature and Ph Dependence In The Three Kinetic Resolutiomentioning
confidence: 99%